An efficient microcontroller-based electronic ballast for high pressure sodium lamps used in street lighting - Omar, Mohd. Hamizan (2013)
Conventional street lighting system with magnetic ballast is cheap and robust, but its operation cannot be dimmed, thus requiring more energy due to 12 hours daily at full load operation. The total energy consumption for street lighting at Universiti Teknologi Malaysia (UTM) reaches approximately 1,238.24 MWh or 2.08% of total energy consumption per annum including core and cable losses. The energy requirement and operating cost for such a system is significantly high and can be possibly reduced by incorporating the potential of microcontroller based electronic ballast. This thesis proposes a control scheme using Pulse Width Modulation (PWM) Atmega32 dimming electronic ballast to replace the existing system. The main aim is to develop a lighting system that is more energy efficient and environmental friendly by using the PWM method to regulate the dimming system. Testing was done on one unit of a 150 W HPS lamp and the result was projected for 956 units. Results show that this new system can provide energy savings of 32.17% with a payback period of 25 months. This translates into 2082.79 metric tons reduction of Carbon Dioxide (CO2) emissions annually. The findings also show that the current Total Harmonic Distortion (THDi) for the whole system is 7.6% for full load operating system, 8.4% for 80% dimming and 10.1% for 50% dimming street lighting. The results conform with all the related standards used for the purpose of this study.